THE PREVALENCE OF CHILD DEFILEMENT AND SUFFERING BY BOYS AND GIRLS IN THIKA SUB-COUNTY - Mwangi, Jedidah Ngina; Ndungo, Prof. Catherine; Masiga, Dr. Casper (International Journal of Gender Studies, 2018)
Purpose: The study aimed at establishing the prevalence of child defilement and suffering by boys and girls in Thika Sub-county. Methods: This study adopted a descriptive design to establish the prevalence of child defilement and suffering by boys and girls in Thika Sub-county. The target population of this study was school going children below 18 years old in selected public primary school of Thika Sub-county. Purposive sampling was used to get a sample of 190, being 30% of the target population of 630 pupils in Thika Sub-county. Two research instruments were considered in collecting the data. These were questionnaire and interviews schedule.. Quantitative data was obtained from pre-coded questions while qualitative data was obtained from open-ended questions and interview schedule responses. Both descriptive statistics and narrative reports were used to produce the analysis report presented in form of tables, graphs, and charts Results: The study findings showed that 18% boys and 23.6% girls were victims of sexual abuse. This high prevalence suggests that child abuse is rampant in Thika sub County. The prevalence corresponds with the UNICEF report, (2000) that, there is wide spread of sexual abuse of children in central Provence. There were 2-3 cases reported in a month at the police station meaning very few cases are reported compared to police report from the findings, who said that they receive at least one case in a week. On the other hand the Doctors in the hospitals reported that they receive eight cases in every week and the most affected gender was girls. In addition the researcher found that both gender are not spared when it comes to child sexual abuse, because the number was almost equal. Unique contribution to theory, practice and policy: The study recommended that, the Kenya police force should be facilitated and motivated as they do their work. This should be in-form of logistical support so that they can easily follow up defilement cases since they would have got transport to go on the ground where the offence would have been committed, hence getting first- hand information and evidence to back up the cases. Keywords: Prevalence, suffering, child defilement, Thika sub county